2004
DOI: 10.1002/hep.20092
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid for treatment of nonalcoholic steatohepatitis: Results of a randomized trial

Abstract: No effective medical therapy is available for all patients with nonalcoholic steatohepatitis (NASH). Ursodeoxycholic acid (UDCA) has been suggested to be of benefit based on open label clinical studies. We randomized 166 patients with liver biopsy-proven NASH to receive between 13 and 15 mg/kg/d of UDCA or placebo for 2 years. End points included changes in liver test results and liver histology at 2 years of therapy. The treatment groups were comparable at entry with regard to age, gender, risk factors for NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
394
1
29

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(433 citation statements)
references
References 31 publications
9
394
1
29
Order By: Relevance
“…Until further data supporting its effectiveness become available, vitamin E is not recommended to treat NASH in diabetic patients, NAFLD without liver biopsy, NASH cirrhosis, or cryptogenic cirrhosis (Strength -1, Quality -C) Ursodeoxycholic acid (UDCA), Omega-3 fatty acids, and Miscellaneous Agents Several studies 126,[137][138][139][140] investigated UDCA (conventional and high doses) to improve aminotransferases and steatosis in patients with NAFLD and liver histology in patients with NASH. All but one study 139 have been proof-of-concept studies with small numbers of participants and/or surrogate endpoints. Notably, a single large multicenter RCT convincingly showed that UDCA offers no histological benefit over placebo in patients with NASH.…”
Section: Vitamin Ementioning
confidence: 99%
See 1 more Smart Citation
“…Until further data supporting its effectiveness become available, vitamin E is not recommended to treat NASH in diabetic patients, NAFLD without liver biopsy, NASH cirrhosis, or cryptogenic cirrhosis (Strength -1, Quality -C) Ursodeoxycholic acid (UDCA), Omega-3 fatty acids, and Miscellaneous Agents Several studies 126,[137][138][139][140] investigated UDCA (conventional and high doses) to improve aminotransferases and steatosis in patients with NAFLD and liver histology in patients with NASH. All but one study 139 have been proof-of-concept studies with small numbers of participants and/or surrogate endpoints. Notably, a single large multicenter RCT convincingly showed that UDCA offers no histological benefit over placebo in patients with NASH.…”
Section: Vitamin Ementioning
confidence: 99%
“…Notably, a single large multicenter RCT convincingly showed that UDCA offers no histological benefit over placebo in patients with NASH. 139 Omega-3 fatty acids, currently approved in the United States to treat hypertriglyceridemia, have been investigated to treat NAFLD both in animal models and in humans. 141 A recent review by Masterton et al, 142 of published literature related to omega-3 fatty acids in NAFLD, found experimental evidence to support their use but the interpretation of human studies was limited by small sample size and methodological flaws.…”
Section: Vitamin Ementioning
confidence: 99%
“…Seven RCTs (639 participants, 21% diabetic; three RCTs with post-treatment histology, five RCTs with a low risk of bias) evaluated UDCA in NAFLD (ESM Table 5) [82][83][84][85][86][87][88].…”
Section: Ursodeoxycholic Acid (Udca)mentioning
confidence: 99%
“…Numerous other antioxidants show efficacy in treating fatty liver diseases and include Nacetylcysteine [166], zinc [167,168], silymarin [169], and ursodeoxycholic acid [170], just to name a few. Please refer to the following excellent review articles for additional information on antioxidant therapy for treatment of fatty liver diseases from multiple causes [144,[171][172][173][174].…”
Section: Are Antioxidants Feasible Treatments For Fatty Liver Disease?mentioning
confidence: 99%